Simulation of CO2 storage and methane gas production from gas hydrates in a large scale laboratory reactor - CASTELLANI, BEATRICE; Rossetti, Giacomo; Tupsakhare, Swanand; ROSSI, Federico; NICOLINI, ANDREA; Castaldi, Marco J. (Journal of Petroleum Science and Engineering, 2016)
This paper focuses on methane recovery from gas hydrates and the thermal assisted CH4-CO2 replacement in the hydrate phase.The experimental investigation was carried out in a 60L reactor, in which the CH4 hydrates were formed with different saturations of the matrix (10%, 30% and 50%) and subsequently dissociated by supplying heat and a simultaneous CO2 stream. The tests simulated the down-hole combustion method for gas production in hydrate reservoirs and the CO2 injection was purposefully set to match the output from the combustion system operating on liquid fuel. CH4-CO2 replacement was studied both via CO2 flow-through experiments and baseline thermal dissociation experiments utilizing heating rates from 50W to 100W. In presence of low hydrate saturation levels, with the 50W heating rate, the CH4–CO2 exchange and CO2 sequestration occurs within the first hours of the tests, while a 100W heating rate resulted in a considerable reduction of favourable regions for CO2 capture. Tests at higher hydrate saturation levels, with a 100W heating rate, show that the addition of CO2 increased the number of moles of CH4 recovered and reduced the length of the test. At higher saturations, the hydrate dissociation process gives an adequate thermostatic effect to counterbalance the higher heating power, and maintain temperatures under the CO2 hydrate equilibrium line. Finally, for a 50W heating rate, carbon balance calculations, in which the CO2 entrapped in the hydrate phase and the CO2 produced during the thermal stimulation process and the combustion of the released CH4, resulted in a substantially negative carbon footprint of the CH4 extraction-CO2 injection process, proving its sustainability.